Rethinking Indonesia’s lighting standard for urban kampung roads (ARTEKS : Jurnal Teknik Arsitektur, 2023)
The latest lighting standard in Indonesia, SNI 7391:2008, emphasizes uniform distribution for road lighting to ensure the safety and accuracy of motorists. However, in urban kampungs, local roads serve as non-commercial public spaces and require lighting that is suitable for human-scale activities. This study examines road lighting in Siwalankerto, Surabaya, and explores how residents' nighttime experiences relate to their perceived adequacy of illumination (PAI). The research involved 26 participants who rated their experiences while using the local road after dark. Nighttime experiences, including pleasantness, willingness to stay, and safety, were compared to illuminance levels and PAI. The findings show a correlation between perceived adequacy of illumination and pleasantness, as well as the willingness to stay in the road space. There was no significant correlation between safety and PAI.
Keywords: Lighting standard; Local road; Perceived adequacy of illumination; Road lighting; Urban kampung